The Effect of Ear Acupuncture Therapy with a Combination of Gotu Kola Tea on Changes in Blood Pressure in Hypertension Cases in Kemandungan Village, Tegal Barat Subdistrict, Tegal City - Darojatin, Ibnati Ulya; Wardoyo, Suwaji Handaru; Sholihah, Imrok Atus (Indonesian Journal of Acupuncture, 2024)
Hypertension is high blood pressure with systolic values above 140 mmHg and diastolic values above 90 mmHg. Ear acupuncture and gotu kola tea are nonpharmacological treatments that can be used to treat hypertension. The purpose of this study was to determine the effect of ear acupuncture therapy with a combination of gotu kola tea on changes in blood pressure in cases of hypertension in Kemandungan Village, Tegal Barat Subdistrict, Tegal City. This study used a research design "Quasy-Experimental Design" with the method of two groups-pretest posttest design. The number of research subjects was 30 people with a purposive sampling technique, which was divided into a control group (ear acupuncture) and an experimental group (ear acupuncture combined with gotu kola tea brewing). The Mann-Whitney test results obtained a significant value of p <0.05 (p = 0.014 and p = 0.013) then H0 is rejected and Ha is accepted so that it can be interpreted that there is an effect of ear acupuncture therapy with a combination of gotu kola tea brewing on changes in blood pressure in cases of hypertension in Kemandungan Village, Tegal Barat Subdistrict, Tegal City with a 6% change in systole and 3% higher diastole than the control group